Drót 6. adás
1. 4th April 1945, end of World War II: history textbooks. 2. Interview with t he chief prosecutor. 3. Elections: candidacy tickets, personal data. 4. Announcing the launching of "Drótháló". 5. Campaign events: 26th March Fidesz faction weekend, Kecskemét, FKgP, Budapest, MDF public forum Ajka, Munkáspárt public forum Vámosmikola, MSZP Carnation Ball Szeged, 27th March MIÉP public forum Pesthidegkút, KDNP rally Székesfehérvár, SZDSZ public forum Jászberény, Vállalkozók Pártja Gárdony. 6. Preview of next Drót program.